Science and Technology from Global and Historical Perspectives - Karagözoğlu, Bahattin; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book provides science and technology ethos to a literate person. It starts with a rather detailed treatment of basic concepts in human values, educational status and domains of education, development of science and technology and their contributions to the welfare of society. It describes ways and means of scientific progresses and technological advancements with their historical perspectives including scientific viewpoints of contributing scientists and technologists. The technical, social, and cultural dimensions are surveyed in relation to acquisition and application of science, and advantages and hindrances of technological developments. Science and Technology is currently taught as a college course in many universities with the intention to introduce topics from a global historical perspective so that the reader shall stretch his/her vision by mapping the past to the future. The book can also serve as a primary reference for such courses.
Definitions and terminologies -- Foundation of science -- Way of inquiring scientific knowledge -- Project planning: an essential procedure needed for a successful project work -- Technology -- Contribution of muslim scientist to technology -- Brief history of western modernization -- technology and its aftermath.
Keywords: Technology; History; Science -- Social aspects; Technology -- Moral and ethical aspects; Environment; Science -- History; Project management; History of Technology; Science and Technology Studies; Ethics of Technology; Environmental Sciences; History of Science; Project Management